EFFECTIVENESS OF MINDFULNESS IN REDUCING ACADEMIC STRESS IN NURSING STUDENTS: A SYSTEMATIC REVIEW - Badrul Munif; Susi Oktaviana; Wahyu Adri Wirawati (The Malaysian Journal of Nursing (MJN), 2020)
Introduction: Academic stress among nursing students increases every year. It is influenced by the dense of academic burden and clinical practice. Because of these conditions, students cannot carry out the study process properly and it leads to poor quality of graduates. Managing the academic stress as soon as possible in nursing students is a necessity. An effective intervention is needed to reduce academic stress in nursing students. Mindfulness is an exercise to build self-awareness in accepting the conditions experienced at present, thus someone is able to build focus in solving the problems encountered. Through a systematic review, this research analyzed the effect of mindfulness as an effort to reduce stress in nursing students. Method: Articles search was conducted by using PICOT framework in EBSCO, Science Direct, and Pub Med. The search was limited to full text articles published from 2009 to 2017. It was obtained six International Journal Articles and subsequently a systematic review was conducted. Result: Based on the search results, there were obtained two articles that used high quality RCT designs and four articles not used RCT designs. All articles used an average length of intervention of 8 weeks. The entire journal articles proved that mindfulness-based intervention can reduce stress. Conclusion: This systematic review highly recommend mindfulness-based intervention to reduce academic stress on nursing students.